The Epidemiology of Rift Valley Fever in Mayotte: Insights and Perspectives from 11 Years of Data. - Raphaëlle Métras; Lisa Cavalerie; Laure Dommergues; Philippe Mérot; W John Edmunds; Matt J Keeling; Catherine Cêtre-Sossah; Eric Cardinale (PLoS Neglected Tropical Diseases)
Rift Valley fever (RVF) is a zoonotic arboviral disease that is a threat to human health, animal health and production, mainly in Sub-Saharan Africa. RVF virus dynamics have been poorly studied due to data scarcity. On the island of Mayotte in the Indian Ocean, off the Southeastern African coast, RVF has been present since at least 2004. Several retrospective and prospective serological surveys in livestock have been conducted over eleven years (2004-15). These data are collated and presented here. Temporal patterns of seroprevalence were plotted against time, as well as age-stratified seroprevalence. Results suggest that RVF was already present in 2004-07. An epidemic occurred between 2008 and 2010, with IgG and IgM peak annual prevalences of 36% in 2008-09 (N = 142, n = 51, 95% CI [17-55]) and 41% (N = 96, n = 39, 95% CI [25-56]), respectively. The virus seems to be circulating at a low level since 2011, causing few new infections. In 2015, about 95% of the livestock population was susceptible (IgG annual prevalence was 6% (N = 584, n = 29, 95% CI [3-10])). Monthly rainfall varied a lot (2-540mm), whilst average temperature remained high with little variation (about 25-30°C). This large dataset collected on an insular territory for more than 10 years, suggesting a past epidemic and a current inter-epidemic period, represents a unique opportunity to study RVF dynamics. Further data collection and modelling work may be used to test different scenarios of animal imports and rainfall pattern that could explain the observed epidemiological pattern and estimate the likelihood of a potential re-emergence.